2003
DOI: 10.1179/016164103771953998
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of interleukin-1 beta levels after acute brain injury

Abstract: Traumatic injury to central nervous system results in the production of inflammatory cytokines via intrinsic mechanisms by neurons, astrocytes and microglia, and extrinsic mechanisms by infiltrating macrophages, lymphocytes and other leukocytes. Interleukin-1 beta is the key mediator of the acute inflammatory host response. While this response is necessary for resolution of the pathologic event, the toxic nature of many of its products can cause significant tissue damage. We analyzed serum interleukin-1 beta l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Furthermore, we are aware of only one previous report that evaluated IL-10 in isolated TBI patients dichotomized by injury severity, albeit in a population of 26 patients that assessed injury severity at 7 days post-injury [ 50 ]. Also, in agreement with previous research, unfavorable patient outcome and mortality were associated with elevated peripheral concentrations of IL-1β, IL-10, and TNF-α [ 32 , 37 , 46 , 48 ]. Importantly, the relationships between cytokines and patient outcome were significant even after controlling for injury severity, suggesting a possible independent role of these mediators in secondary injury pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we are aware of only one previous report that evaluated IL-10 in isolated TBI patients dichotomized by injury severity, albeit in a population of 26 patients that assessed injury severity at 7 days post-injury [ 50 ]. Also, in agreement with previous research, unfavorable patient outcome and mortality were associated with elevated peripheral concentrations of IL-1β, IL-10, and TNF-α [ 32 , 37 , 46 , 48 ]. Importantly, the relationships between cytokines and patient outcome were significant even after controlling for injury severity, suggesting a possible independent role of these mediators in secondary injury pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Though we did not identify differences in a number of previously identified TBI inflammatory markers such as IL-1β, IL-6 and IL-10, these markers have typically been evaluated in the acute stages after severe TBI [ 52 , 76 78 ]; conversely, our cohort was ostensibly healthy, and the median time from last concussion was approximately two years ( Table 1 ). Furthermore, while numerous cytokines have been found elevated for up to three months after severe TBI [ 79 ], few studies have evaluated the chronic inflammatory response after concussion.…”
Section: Discussionmentioning
confidence: 80%
“…From previous studies it is known that intensity of inflammation may predict the extent of brain damage [34], and consequently clinical presentation and outcome [35]. Moreover, we recently reported that a functional polymorphism in the IL-1RN gene was associated with hemorrhagic events after traumatic brain injury [31].…”
Section: Discussionmentioning
confidence: 99%